Comparative transcriptome sequencing analysis of female and male Decapterus macrosoma - Zizi Cai; Shigang Liu; Wei Wang; Rui Wang; Xing Miao; Puqing Song; Binbin Shan; Liangming Wang; Yuan Li; Longshan Lin (PeerJ, 2022)
Sexual growth dimorphism is a common phenomenon in teleost fish and has led to many reproductive strategies. Growth- and sex-related gene research in teleost fish would broaden our understanding of the process. In this study, transcriptome sequencing of shortfin scad Decapterus macrosoma was performed for the first time, and a high-quality reference transcriptome was constructed. After identification and assembly, a total of 58,475 nonredundant unigenes were obtained with an N50 length of 2,266 bp, and 28,174 unigenes were successfully annotated with multiple public databases. BUSCO analysis determined a level of 92.9% completeness for the assembled transcriptome. Gene expression analysis revealed 2,345 differentially expressed genes (DEGs) in the female and male D. macrosoma, 1,150 of which were female-biased DEGs, and 1,195 unigenes were male-biased DEGs. Gene Ontology (GO) and Kyoto Encyclopedia of Genes and Genomes (KEGG) analyses showed that the DEGs were mainly involved in biological processes including protein synthesis, growth, rhythmic processes, immune defense, and vitellogenesis. Then, we identified many growth- and sex-related genes, including Igf, Fabps, EF-hand family genes, Zp3, Zp4 and Vg. In addition, a total of 19,573 simple sequence repeats (SSRs) were screened and identified from the transcriptome sequences. The results of this study can provide valuable information on growth- and sex-related genes and facilitate further exploration of the molecular mechanism of sexual growth dimorphism.